2004
DOI: 10.1029/2003jc002045
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing oceanography of a harmful algal bloom off the coast of southeastern Vietnam

Abstract: [1] Harmful algal blooms (HABs) in the southeastern Vietnamese coastal waters have caused large economic losses in aquacultured and wild fisheries in recent years; however, there have been few oceanographic studies on these HAB events. The present study reports an extensive HAB off southeastern Vietnamese waters during late June to July 2002 with in situ observations and analyzes the oceanographic conditions using satellite remote sensing data. The HAB had high chlorophyll a (Chl a) concentrations (up to 4.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 20 publications
(30 reference statements)
3
88
0
Order By: Relevance
“…strains of P. globosa derived from the South China Sea and the Vietnam coast; Tang et al 2004). P. pouchetii AJ01 also did not form colonies at all tested temperatures (confirming the results of Malin et al 1998), suggesting that the role of temperature is minor in controlling the development of colonies.…”
Section: Solitary Vs Colonial Formssupporting
confidence: 70%
See 1 more Smart Citation
“…strains of P. globosa derived from the South China Sea and the Vietnam coast; Tang et al 2004). P. pouchetii AJ01 also did not form colonies at all tested temperatures (confirming the results of Malin et al 1998), suggesting that the role of temperature is minor in controlling the development of colonies.…”
Section: Solitary Vs Colonial Formssupporting
confidence: 70%
“…They have both an ecological impact on the local food web and a negative economic influence on tourism. Dense blooms have also been observed off the coasts of southeast China , Vietnam (Tang et al 2004), and Norway (Larsen et al 2004). The clones isolated from Chinese and Norwegian waters have hemolytic properties as well (Shen et al 2004, van Rijssel et al 2007.…”
Section: Introductionmentioning
confidence: 89%
“…The study area is located in a relatively oligotrophic tropical-subtropical ocean (Tang et al, 1999(Tang et al, , 2004b. Averaged winter SST of about 24.3°C promotes the growth of phytoplankton (Peñaflor et al, 2007), and monthly mean photosynthetically active radiation (PAR) observed in winter at the study area is high (Chen et al, 2006).…”
Section: The Region Of the Phytoplankton Bloomsmentioning
confidence: 99%
“…Though the SCS is a relatively oligotrophic tropical-subtropical ocean (Tang et al, 1999(Tang et al, , 2004b, winter phytoplankton blooms occur in the vicinity of Luzon Strait in certain years (Tang et al, 1999;Chen et al, 2006;Peñaflor et al, 2007). Tang et al (1999) first reported this phenomenon appeared in the winters of 1981, 1982 and 1984 using Coastal Zone Color Scan (CZCS) data.…”
Section: Introductionmentioning
confidence: 99%
“…Mass fish mortalities have been linked to Phaeocystis spp. blooms in the Irish Sea (Rogers and Lockwood, 2009) and south-eastern Vietnamese coastal waters (Tang et al, 2004). The mass transport and sedimentation of a P. globosa bloom in 2001 in the Oosterschelde estuary (North Sea) caused anoxic conditions that led to the mass mortality of 10 million kg of Mytilus edulis with a market value of 15 to 20 million euro (Peperzak and Poelman, 2008).…”
Section: Discussionmentioning
confidence: 99%